Dikotomi Pemilihan Kepala Daerah: Demokrasi dan Dinasti Perspektif Islam - Jamaludin, Jujun (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2023)
Indonesia is a large country and is crowned as the largest archipelagic country inthe world. Indonesia consists of various ethnic groups, languages and religions.However, when the local elections take place, different perceptions from thecommunity often arise, issues that often occur include: legal issues, historicalissues, and